2013
DOI: 10.1038/aps.2013.124
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitor BIIB021 enhances triptolide-induced apoptosis of human T-cell acute lymphoblastic leukemia cells in vitro mainly by disrupting p53-MDM2 balance

Abstract: Aim: To investigate the effects of BIIB021, an inhibitor of heat shock protein 90 (Hsp90) alone or in combination with triptolide (TPL) on T-cell acute lymphoblastic leukemia (T-ALL) and the mechanisms of action. Methods: Human T-ALL cells line Molt-4 was examined. The cell viability was measured using MTT assay. Apoptotic cells were studied with Hoechst 33258 staining. Cell apoptosis and cell cycle were analyzed using flow cytometry with Annexin V/PI staining and PI staining, respectively. The levels of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In addition, aberrantly up-regulated Hsp90, promoting tumor cell survival and growth, has been described in human hematologic malignancies. such as MM [35], chronic lymphocytic leukemia [22], acute lymphoid leukemia [36], acute myeloid leukemia [37], and diffuse large B cell lymphoma [38]-altogether, malignancies that are subject to ASCT. This implicates that pharmacological Hsp90 inhibition could serve as a bridging concept to suppress residual tumor growth temporally upon ASCT until the GvL reaction has been fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aberrantly up-regulated Hsp90, promoting tumor cell survival and growth, has been described in human hematologic malignancies. such as MM [35], chronic lymphocytic leukemia [22], acute lymphoid leukemia [36], acute myeloid leukemia [37], and diffuse large B cell lymphoma [38]-altogether, malignancies that are subject to ASCT. This implicates that pharmacological Hsp90 inhibition could serve as a bridging concept to suppress residual tumor growth temporally upon ASCT until the GvL reaction has been fully developed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other HSP90 inhibitors, BIIB021 is also reported to block the constitutive NF-κB activity in cancers 32 and induce apoptosis by disrupting the p53-MDM2 balance in leukemia. 31 Moreover, He et al 43 proved for the first time that BIIB021 could also induce autophagic response as evidenced by the formation of autophagosome in chronic myeloid leukemia (CML), which is related to the Akt-mTOR-Ulk1 signaling pathway. Besides, this chemical compound was also reported to sensitize esophageal squamous cell carcinoma and head and neck squamous cell carcinoma to radiation.…”
Section: Initial Attempts To Target Hsp90 From Natural Productsmentioning
confidence: 99%
“…In malignant cells, BIIB021 and triptolide, as a single drug, modulate PI3K/Akt and NF-kB signal pathways, and thereby have cytotoxic activities [15][16][17][18][19][20][21][22]. Meanwhile, BIIB021 causes cell death by regulating mTOR-Ulk1 signal pathway in chronic myeloid leukemia cells [23].…”
Section: Synergistic Activity Of Biib021 With Triptolide Is Involved mentioning
confidence: 99%
“…With regard to thyroid cancer, it was shown that triptolide induced cytotoxicity via downregulation of NF-kB in ATC cells [16][17][18]. Although the combined effect of BIIB021 with triptolide was explored in acute lymphoblastic leukemia cells [19], the impact of BIIB021 in combination with triptolide on survival of thyroid carcinoma cells has not been identified.…”
Section: Introductionmentioning
confidence: 99%